Structure of the dailies la Hora y Crónica de la Tarde de Loja - Ecuador and the application of Web 2.0 tools in their digital versions - Yaguache Quichimbo, J. (2010)
Organizations like the society are experiencing an accelerated process of change. This dynamic necessarily generate permanent changes in the structure and strategies of each institution. According to current trends in the cultural industry is necessary to make changes, which encompass the new structures of business organizations in the future be given. It is a challenge facing the media, because tastes and preferences of society in the consumption of information, are moving quickly through the digital revolution. The huge advances in technology and the Internet and social change and communication that has led, and continues to advocate, are what have caused a radical change in the media and parallel to, the use of tools and how thinking of your audience. Traditional media on the Web begin to create a philosophy focused on becoming true cibermedios, one of the proposals is the inclusion of 2.0 tools in their websites, like blogs, social networks, microblogging, etc.